Challenges and Opportunities for Regular Teachers in the Implementation of Assessments for Students with Special Needs in Inclusive Education Provider School - Kartini, Ade; Aprilia, Imas Diana (Angstrom Centre of Education, 2022)
Teacher’s misunderstanding in carrying out the assessment has the potential to lead to learning failure. Assessment is considered a routine learning activity but is also considered an additional burden. The purpose of this study was to obtain an overview of the challenges and opportunities faced by regular teachers regarding the assessment of students with special needs in their classrooms. The research method used is descriptive qualitative. Data was collected through interviews, observation, and documentation, with the research subject being teachers in one of the elementary schools in Sumedang Regency. The results of the study indicate the low ability of regular teachers in the preparation of assessment instruments and their implementation; difficulties in developing learning programs and management; the complexity and high teaching load related to a large number of students with special needs in the class; lack of coordination between regular teachers and special assistant teachers (GPK) as well as special education teachers, and limited competency improvement services that regular teachers can access. The opportunity is that teachers know the importance of assessment, more assessment information can be accessed, frequent training and technical guidance that regular teachers can participate in, open collaboration with special education teachers, and easy school accommodation. The conclusion is still many challenges faced by regular teachers in carrying out assessments so a concrete program is needed that can create opportunities to improve the ability of regular teachers in carrying out assessments.